The influence of intrinsic motivation on an endurance field tes - Tsigilis, N. (The Journal of Sports Medicine and Physical Fitness, 2005)
Aim: The aim of the present study was to examine the influence of various aspects of intrinsic motivation on the levels of performance in an endurance field test. Methods: The sample of the study consisted of 144 undergraduate Physical Education students. A Greek version of the Intrinsic Motivation Inventory (IMI) was administered to participants after the completion of the 20 m shuttle field test. Results: The 20 m shuttle run test was significantly and positively associated with the interest-enjoyment, perceived competence and effort-importance subscales. Regression analysis showed that only the perceived competence subscale could significantly contribute to the prediction the 20 m shuttle run scores. Conclusion: It was concluded that the perceived competence subscale of the IMI significantly predicted 20 m shuttle run performance and thus could be used to explain an additional percent of the variation in the participants' performance scores.